2022
DOI: 10.2196/36111
|View full text |Cite
|
Sign up to set email alerts
|

A Medical-Grade Polycaprolactone and Tricalcium Phosphate Scaffold System With Corticoperiosteal Tissue Transfer for the Reconstruction of Acquired Calvarial Defects in Adults: Protocol for a Single-Arm Feasibility Trial

Abstract: Background Large skull defects present a reconstructive challenge. Conventional cranioplasty options include autologous bone grafts, vascularized bone, metals, synthetic ceramics, and polymers. Autologous options are affected by resorption and residual contour deformities. Synthetic materials may be customized via digital planning and 3D printing, but they all carry a risk of implant exposure, failure, and infection, which increases when the defect is large. These complications can be a threat to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Preclinical studies to increase research reproducibility [260,263] and for clinical studies in general in the field of large bone defect treatment using 3D-printed scaffolds can only be performed in purposefully planned and well-powered multicentre large-scale collaborative research projects to have the possibility to correct confounding factors related to host and soft tissue while investigating the respective implant for different defect sizes or for different surgical indications [157,264,265]. Furthermore, as bone defects are rare but very complex diseases with a dramatic socio-economic impact on the healthcare system, there are many open questions that may be better understood in the future through the use of artificial intelligence methods-from predictive models and cost analyses to personalised treatment strategies [266]; however, these methods first need to be validated in preclinical and clinical studies.…”
Section: Challenge Interdisciplinary (Stakeholder Workhop) Approachmentioning
confidence: 99%
“…Preclinical studies to increase research reproducibility [260,263] and for clinical studies in general in the field of large bone defect treatment using 3D-printed scaffolds can only be performed in purposefully planned and well-powered multicentre large-scale collaborative research projects to have the possibility to correct confounding factors related to host and soft tissue while investigating the respective implant for different defect sizes or for different surgical indications [157,264,265]. Furthermore, as bone defects are rare but very complex diseases with a dramatic socio-economic impact on the healthcare system, there are many open questions that may be better understood in the future through the use of artificial intelligence methods-from predictive models and cost analyses to personalised treatment strategies [266]; however, these methods first need to be validated in preclinical and clinical studies.…”
Section: Challenge Interdisciplinary (Stakeholder Workhop) Approachmentioning
confidence: 99%
“…Moreover, the mPCL-HA Voronoi scaffolds tested in this study exhibited a higher modulus of elasticity than the mPCL composite scaffolds currently used clinically for the treatment of long bone defects and 3D-printed with a rectilinear filling pattern [ 2 , 3 ] (Young's modulus of 22.2 MPa [ 16 ]). Stress–strain curves in the present study were observed to have very similar deformation behaviour to the PCL-tricalcium phosphate (wt 80 %:20 %) scaffolds with rectilinear layer structure [ 44 ], which have already been successfully used in clinical practice [ 2 , 3 , 45 , 46 ]. Complemented by an observed porosity of >50 % of the mPCL-HA Voronoi scaffolds, which we know to be fundamentally capable of facilitating the necessary neovascularization and new (bone) tissue formation [ 2 , 3 , 6 ], we have assessed the scaffolds as suitable for investigating and comparing different scaffold-BG constructs.…”
Section: Discussionmentioning
confidence: 60%